2014
DOI: 10.3109/00365521.2014.950692
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of TNM staging in colorectal cancer: a review of current culprits, the modern role of morphology and stepping-stones for improvements in the molecular era

Abstract: Colorectal cancer (CRC) is the third most common cancer worldwide. Survival is largely stage-dependant, guided by the tumor-node-metastases (TNM) system for TNM assessment. Histopathological evaluation, including assessment of lymph node status, is important for correct TNM staging. However, recent updates in the TNM system have resulted in controversy. A continued debate on definitions resulting in potential up- and downstaging of patients, which may obscure survival data, has led the investigators to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
73
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 101 publications
0
73
0
Order By: Relevance
“…In a recent report, Lea et al described the limitations of the current TNM staging system in predicting the outcome of patients with CRC [20]. They suggested that the immune cell density in the stromal environment could be a better prognostic marker.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent report, Lea et al described the limitations of the current TNM staging system in predicting the outcome of patients with CRC [20]. They suggested that the immune cell density in the stromal environment could be a better prognostic marker.…”
Section: Discussionmentioning
confidence: 99%
“…Galon et al introduced the ‘immunoscore (IS)’, a value based on the density of CD3 + and CD8 + lymphocytes in the tumor center (CT) and invasive margin (IM) [1719]. Moreover, some authors have reported that the IS method is superior to the current tumor-node-metastases (TNM) staging system, especially in colon cancers [20, 21]. However, the evidence is limited to stages I–III of the disease [18, 22].…”
Section: Introductionmentioning
confidence: 99%
“…This becomes important as the current Tumour-Node-Metastasis (TNM) staging relies heavily on nodal status (with pN0 or pN+ for no or presence of node metastasis, respectively). Notably, TNM staging, although in widespread use, is imprecise with risk of both over-and undertreatment (13). Therefore, including information that may enhance staging precision beyond the lymph node status is needed.…”
Section: Conclusion: There Is a Correlation Between Blood Cd3 + And Cmentioning
confidence: 99%
“…However, a pathological confirmation using biopsy or FNA is necessary for a definitive diagnosis of prostate cancer [22, 23] because of the high incidence of both cancers in elderly patients. Differences in pathology between prostate and rectal cancers, including cytoarchitecture, glandular architecture, cellular pleomorphism, and mucosecretion patterns, can facilitate a correct diagnosis [24]. In rectal adenocarcinoma, tumor cells form irregular tubular structures, have multiple lumens, and have reduced stroma [25].…”
Section: Discussionmentioning
confidence: 99%